Effect of Intensive Blood Pressure Reduction on Left Ventricular Mass, Structure, Function, and Fibrosis in the SPRINT-HEART. Issue 2 (August 2019) - Upadhya, Bharathi; Rocco, Michael V.; Pajewski, Nicholas M.; Morgan, Tim; Blackshear, Joseph; Hundley, William Greg; Oparil, Suzanne; Soliman, Elsayed Z.; Cohen, Debbie L.; Hamilton, Craig A.; Cho, Monique E.; Kostis, William J; et al.
Abstract : In observational studies, left ventricular mass (LVM) and structure are strong predictors of mortality and cardiovascular events. However, the effect of hypertension treatment on LVM reduction and its relation to subsequent outcomes is unclear, particularly at lower blood pressure (BP) targets. In an ancillary study of SPRINT (Systolic Blood Pressure Intervention Trial), where participants were randomly assigned to intensive BP control (target systolic BP target <120 mm Hg) versus standard BP control (<140 mm Hg), cardiac magnetic resonance imaging was performed at baseline and 18-month follow-up to measure: LVM, volumes, ejection fraction, and native T1 mapping for myocardial fibrosis. At baseline, 337 participants were examined (age: 64±9 years, 45% women); 300 completed the 18-month exam (153 intensive control and 147 standard control). In the intensive versus standard BP control group at 18 months, there was no difference in change in LVM (mean±SE =−2.7±0.5 g versus −2.3±0.7 g; P =0.368), ejection fraction, or native T1 ( P =0.79), but there was a larger decrease in LVM/end-diastolic volume ratio (−0.04±0.01 versus −0.01±0.01; P =0.002) a measure of concentric LV remodeling. There were fewer cardiovascular events in the intensive control group, but no significant association between the reduced events and change in LVM or any other cardiac magnetic resonance imaging measure. In SPRINT-HEART, contrary to our hypothesis, there were no significant between-group differences in LVM, function, or myocardial T1 at 18-month follow-up. These results suggests that mediators other than these LV measures contribute to the improved cardiovascular outcomes with intensive BP control. Abstract : Supplemental Digital Content is available in the text.